Meningkatkan Minat Belajar Matematika Siswa Menggunakan Model Project Based Learning di Kelas VIII SMP Negeri 3 Aek Kuo Labuhanbatu Utara - Tamba, Hergustison; Harahap, Amin; Nst, Jamaluddin Abduh (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2024)
This study aims to determine how implementing the Project Based Learning (PjBL) learning model can improve the results and interest in learning mathematics for Class VIII Students of SMPN 3 Aek Kuo when implementing Project based learning model (PjBL. This study used a qualitative approach with the Classroom Action Research (CAR) type. Datacollection techniques in this study used instruments, i.e., observation sheets, LKPD, final cycle tests, and questionnaires on students' interest in learning mathematics. The research subjects were 24 students in class VIII-1, and the object of research was the PjBL model with a cooperatif method and presentation. The results of the data analysis showed an increase in the average value of student learning outcomes and interest in each cycle and ended up in the second cycle. The percentage of students who completed increased starting from 74.2% in Cycle I, and endedwith 87.1% in Cycle II. Meanwhile, the number of students who were at least interested also increased from 65% in Cycle I, ending with 87% in Cycle II. The PjBL model was successfully implemented due to discussions on diferent action plans with observers, which were carried out following the results of the previous cycle's reflections.